After all, land belongs to the state: examining the benefits of land registration for smallholders in Ethiopia - Yami, Mastewal; Snyder, Katherine A. (Wiley, 2016)
The role of land registration in reducing rural poverty has been debated for several decades. This article analyses the impacts of land registration on land rentals, security of land tenure, disputes over land, use of credit facilities from formal financial institutions and gender access and control over land. Our findings are based on data collected between April and December 2011 in irrigation systems in three regional states of Ethiopia using in-depth interviews and field surveys. Land registration has a positive influence on land rentals by reducing the fear of landholders in losing land to renters. Important benefits of land registration also include enhancing tenure security through ensuring usufruct rights over land and addressing the conflicts that arise from the competition to access irrigable land. Joint land titling secures women's access to land and encourages women's decision-making on land rentals, input use, cropping patterns and the marketing of harvest from irrigable plots. While land registration allows for improved tenure security, gender equity and reduced disputes over land, it does little to facilitate access to credit or increase the use of farm inputs. The findings suggest that more work needs to be carried out to translate the benefits of land registration into improved livelihoods by increasing investment in farm inputs, production of high value, off-season crops and increase market participation. Copyright © 2015 John Wiley & Sons, Ltd.